Comparison of Effects of Smoking and Smokeless Tobacco “Maras Powder” Use on Humoral Immune System Parameters - Murat Aral; Hasan Cetin Ekerbicer; Mustafa Celik; Pınar Ciragil; Mustafa Gul (Mediators of Inflammation)
Background. The aim of this study is to assess the impacts of “Maras powder” and cigarette smoking on the parameters of the humoral immune system. Material and Methods. One hundred seventy seven subjects were included in the study. The IgA, IgG, IgM, C3 and C4 levels were detected via nephelometric method. Results. In1.4% of the control group IgM levels were below normal where it was 10.8% and 18.6% in Maras powder group and in cigarette smoking group respectively. The IgM levels of both groups were significantly lower compared to the control group (P<.05). Nonetheless, the IgE levels of Maras powder group and smoking group were found to be remarkably higher compared to the control group (P<.01). Conclusion. Effects of Maras powder on humoral immune response were found to be similar to that of smoking.